NEW DATA ON THE AGE OF THE SIMONI MELANGE, NORTHERN MIRDITA OPHIOLITE NAPPE, ALBANIA - Chiari, Marco; Bortolotti, Valerio; Marcucci, Marta; Principi, Gianfranco (Ofioliti, 2007)
In the Albanian sector of the Dinaric-Hellenic Chain, the ophiolites have been subdivided into two parallel belts: the Western Belt (WB) and the Eastern Belt, due to their different stratigraphical, petrological and geochemical characteristics: WB represents oceanic lithosphere generated at a mid-oceanic ridge (MOR ophiolites), EB represents an oceanic basin developed over a subduction zone (SSZ ophiolites) (ISPGJ-IGJN, 1990; Beccaluva et al., 1994; Bortolotti et al., 1996, and bibl. therein). EB overthrust westwards WB. The radiolarian cherts (Kalur Cherts) covering the volcanites of both the successions have the same ages, comprised between latest Bajocian-early Bathonian (UAZones 5 of Baumgartner et al., 1995) and middle Callovian-early Oxfordian (UAZones 8) (Chiari et al., 2004, and bibl. therein). Thin levels of radiolarian cherts intercalated in the basalts of EB have late Bajocian to latest Bajocian-early Bathonian ages (UAZones 4-5) (Chiari et al., 1994 and Chiari et al., 2004). A “blocks in matrix-type” sedimentary mélange, the Simoni Mélange, unconformably covers both the successions, indistinctly lying on the radiolarian cherts or on the upper portions of the underlying volcanites (Bortolotti et al., 1996; Carosi et al., 1996). It grades upwards to the Firza Flysch (latest Tithonian-Valanginian age after Shallo 1991; Gardin et al., 1996), a pelagic sediment with frequent ophiolitebearing polimict pebbly sandstones and mudstone intercalations. The mélange includes blocks of different sizes (up to several hundred meters) of continental derived (predominant) and ocean derived rocks, in a shaly matrix. It can be interpreted as “syn-orogenic....deposited after the inception of ophiolite deformation” (Bortolotti et al., 1996). The age of the mélange was indirectly determined, being comprised between middle Callovian-early Oxfordian, the more recent age found at the top of the Kalur Cherts (Marcucci and Prela, 1996), and the latest Tithonian-early Berriasian?, found at the base of the Firza Flysch (Gardin et al., 1996). The aim of this note is to present new biostratigraphical data that define a more precise age of the Simoni Mélange, dating a cherty-silty level found at the top of the Kalur Cherts near the Lumi i Zi (northern Albania).